Sentinel Node Biopsy in Pediatric Patients: The Experience in a Single Institution - Dall'Igna, Patrizia; De Corti, Federica; Alaggio, Rita; Cecchetto, Giovanni (European Journal of Pediatric Surgery, 2014)
Sentinel lymph node biopsy (SLNB) is an established staging technique in many malignancies, but reports describing this procedure for the evaluation of regional lymph nodes in childhood and adolescents are still scarce. SLNB has progressively gained a role in the staging of pediatric melanoma and some histotypes among soft tissue sarcomas (rhabdomyosarcoma, synovial sarcoma, epithelioid sarcoma, and clear cell sarcoma). We report our experience with 29 patients who were evaluated with SLNB during the past 12 years: 9 alveolar rhabdomyosarcoma, 1 embryonal rhabdomyosarcoma, 7 Ewing Sarcoma/pPNET, 1 clear cells sarcoma, 2 epithelioid sarcoma, 1 epithelioid sclerosing fibrosarcoma, 3 myxoid liposarcoma, 1 adult fibrosarcoma, 1 malignant peripheral nerve sheath tumor, 1 undifferentiated sarcoma, 1 sarcoma not otherwise specified, and 1 melanoma. All, but one, patients underwent a lymphoscintigraphy, and in more than half of the patients, an intraoperative lymphatic mapping with a blue dye injection was performed. In our experience, SLNB was a feasible and reliable technique that allowed a targeted sampling of regional lymph nodes. This technique avoids aggressive operations or random biopsies, leading to an accurate staging without complications. Recently new imaging techniques, such as positron emission tomography–computed tomography scan, have obtained good results in identifying distant and lymphatic metastases, but they have been found to be less reliable than SLNB, especially for small volume metastatic nodal disease in sarcoma.
Keywords: soft tissue sarcoma; melanoma; sentinel node biopsy